The Effect of Service Quality and Price on Customer Satisfaction and Repurchase Intention (Case Study at Crown Prince Hotel Surabaya) - Tri Wahyu Putra Susanto; I Nyoman Sudapet; Hamzah Denny Subagyo; Joko Suyono (Yayasan Ahmar Cendekia Indonesia, 2021)
The aim of this study: (1) to analyze the effect of Service Quality on Customer Satisfaction, (2) to analyze the effect of prices on Customer Satisfaction, (3) to analyze the effect of Service Quality on Repurchase Intention, (4) to analyze the effect of Price on Repurchase Intention, (5) to analyze the effect of Customer Satisfaction on Repurchase intention. This research is quantitative research. The population and samples were distributed to 86 respondents. Data collection techniques using a questionnaire. The data analysis used is Convergent Validity, Discriminant Validity, Reliability and Average Variance Extracted (AVE). The results of the study show that the influence of Service Quality variable (X1) on Customer Satisfaction (Y1) is significant at 0,000. Customer Quality Variable (X1) is not significant with the Repurchase Intention (Y2) variable of 0.225. Based on the correlation for the Price variable (X2) to customer satisfaction (Y1) of 0.020. And the price variable (X2) is significant with the Repurchase Intention (Y2) variable of 0,000. And the Customer Satisfaction variable (Y1) is significant with the Repurchase Intention (Y2) variable of 0,000. The results of this study indicate that, compared to service quality, Price has a stronger influence on customer satisfaction, which leads to a Buyback Interest.